Verbascoside from Verbena incompta is a plant root growth inhibitor. Issue 7 (18th May 2021) - Date, Tomonori; Shigeno, Kanamu; Hiroshima, Megumi; Seo, Kohei; Sato, Masashi; Tebayashi, Shinichi; Sato, Shushi
ABSTRACT: The use of biopesticides has expanded rapidly in recent years; however, their use in weed control is less advanced. Herein, we describe the development of a weed control agent by screening 208 plant extracts (104 species) for their plant growth-inhibition activities, which resulted in 142 active samples (from 89 plant species). Verbascoside, isolated from the shoots of Verbena incompta, was identified as a growth inhibitor against rice root (EC50, 1.75 m m ), and its root growth-inhibition activity was also confirmed in radish, tomato, and Lotus japonicus . Verbascoside is composed of hydroxytyrosol (EC50, 12.51 m m ) and caffeic acid (EC50, 4.08 m m ), 2 poorly water-soluble phenolic components with weak growth-inhibition activities, and 2 sugars, which are more soluble but inactive. The plant apparently developed a more active and highly soluble compound by condensing these 4 components. We conclude that a biopesticide containing verbascoside may be useful for weed-control purposes. Graphical Abstract: